Usporedna analiza arhitektura i scenarija uvođenja optičke pristupne mreže sljedeće generacije : doktorski rad - Havić, Zijad; Mikac, Branko (Zagreb: Z. Havić ; Fakultet elektrotehnike i računarstva, 2014)
SAŽETAK: U disertaciji se predlaže metodologija za usporednu analizu arhitektura i scenarija uvođenja optičkih pristupnih mreža sljedeće generacije uz pretpostavku niske početne i očekivane gustoće korisnika. Metodologija uključuje model i metode analize koji se primjenjuju u proračunu troškova, raspoloživosti i potrošnje energije pristupne mreže. Metode su implementirane u okviru programskog alata CABE. Alat omogućuje, također, analizu osjetljivosti performansi i troškova mreže na varijaciju ulaznih parametara. Metodologija je verifcirana na četiri studijska slučaja, specifična područja uvođenja optičkih pristupnih mreža koja se razlikuju po gustoći korisnika i po naslijeđenoj mrežnoj infrastrukturi. Analiza troškova, raspoloživosti i potrošnje energije provedena je za starogradska, gradska, prigradska i ruralna područja. U disertaciji se predlaže, također, integrirana mjera pogodna za ocjenu pogodnosti tehnologija pristupne mreže i njihovu usporednu analizu. Predložena metodologija tehno-ekonomske analize primjenjiva je na pristupne mreže u različitim zemljama uz primjenu lokalnih parametara. - KLJUČNE RIJEČI: Optička pristupna mreža sljedeće generacije, model troškova, raspoloživost, potrošnja energije, analiza osjetljivosti
SUMMARY: Residential and business broadband is increasingly being seen as an accelerator for an economic growth. Deployment of advanced broadband access networks is a prerequisite for the continuous development and success. The thesis proposes the methodology for comparative analysis of architectures and scenarios of the next generation optical access networks deployments, assuming low initial and expected density of users. The approach of telecom operator using Digital Subscriber Line (DSL) technology is compared to entry strategies based on Fibre-to the-Home in order to evaluate the financial feasibility of residential broadband deployment in different geographical areas. The methodology includes the model and analysis methods that are applied in evaluation of access network cost, availability and power consumption. A fundamental assumption in residential and business broadband deployment is that the required investments are based on financially feasible premises. The methods are implemented in the CABE software tool. The tool enables sensitivity analysis of network performances and costs to variation of input parameters. In contrast to existing static methods of evaluating financial feasibility the thesis argues that properties of the networks and services need to be related to competitive interactions between infrastructures when evaluating financial feasibility, energy consumption and availability. The thesis is divided into eight chapters, where the first one analyses properties of packet-based multimedia services and performs quantitative forecasting of near-future transmission requirements. The second chapter analyses residential and business broadband deployment based on Digital Subscriber Line technology compared to Fibre-to-the-Home. Fourth chapter analyses parts of models and other experts investigation. Fifth and sixth chapters analyse energy consumption and availability. The seventh and eighth chapters explain programming tool and develops model that calculates revenues and estimates financial feasibility, energy consumption and availability. The analysis is applied to the study case, using a dataset from the BH Telecom. The results show that the future of residential broadband networks is based on converged voice, video, and data services. While these services (triple play), can be expected to raise transmission requirements from 20 Mbit/s to 50-100 Mbit/s in the next five years, thesis concludes that there exist more requirements for FTTH rather than DSL. DSL infrastructure is upgraded to meet subscribers requirements. Copper loop lengths determine maximum transmission throughput and can limit service selection and thereby revenues. Upgrade strategies are based on co-locating old equipment in existing copper aggregation nodes. In the case of BH, there are two levels of aggregation points. The first is located on average 0.7-1.6 km from customer premises (Fiber-to-the-Curb), enabling on average 7-16 Mbit/s in transmission throughput, while the second is on average 70 – 210 m from customer premises (Fiber-to-the Building), enabling transmission throughput of 52-90 Mbit/s. The methodology is verified on four case studies — specific areas of optical access network deployments — that differ according to user density and inherited network infrastructure. Analyses of costs, availability and power consumption were carried out for the old parts of the city, as well as for the urban, the suburban and the rural areas. Selection of the proper location of equipment and timing of deployment is a key variable for telecoms operators. Price of equipment can change significantly depending on global deployment trends. In the thesis is proposed an integrated measure suitable for assessment of access network technologies and their comparative analysis. The proposed methodology of techno-economic analysis is applicable to access networks in different countries by applying local parameters. - KEYWORDS: Next generation optical access network, cost model, availability, power consumption, sensitivity analysis
Na spor. nasl. str. naslov na eng. jeziku: Comparative analysis of architectures and deployment scenarios of next generation optical access network : doctoral thesis
Bibliografija: str. 111 - 114. - Sažetak na eng. i hrv. jeziku. - Životopis [uključuje i popis radova autora]